Dziecko nieśmiałe - Nikel, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The monograph provides an overview of specific issues related to child shyness and is divided into seven chapters. The first three chapters delve into the complex nature of a child's shyness, exploring various definitions of shyness, essential characteristics of a shy child, symptoms of shyness, different types of shyness, significant correlates of shyness, as well as the role that culture and the child`s gender play in shaping shyness.
Keywords: dziecko nieśmiałe; nieśmiałość; uwarunkowania nieśmiałości; typy nieśmiałości; rozwój nieśmiałości; korelaty nieśmiałości; nieśmiali uczniowie; psychologia; child`s shyness; determinants of shyness; types of shyness; development of shyness; correlates of shyness; shy students